Communication and coordination as drivers of safety behaviours and outcomes in coal-fired power plants - Kadir Arifin; Mohamad Xazaquan Mansor Ali; Azlan Abas; Mohammad Lui Juhari (PLoS ONE, 2026)
Effective communication and coordination are vital for promoting safety in high-risk industries. While widely regarded as key drivers of safety behaviour, their direct and indirect effects on safety outcomes such as workplace accidents, near misses, fatalities, and lost-time injuries are not well understood, particularly in coal-fired power plants. The study investigates the influence of communication and coordination practices on safety behaviour and their subsequent impact on actual safety outcomes in Malaysian coal-fired power plants. 340 participants from five coal-fired power plants in Peninsular Malaysia participated in a quantitative cross-sectional survey. Stratified random sampling was employed to ensure balanced managerial and non-managerial staff representation. A systematic questionnaire with 60 items was used to gather data. It was divided into four sections: safety outcomes (accidents, near misses, fatalities, and lost-time injuries), safety behaviour dimensions (compliance, involvement, motivation, and knowledge), and demographic data. Five-point Likert scales modified from previously approved instruments were used to measure each issue. Partial Least Squares Structural Equation Modelling (PLS-SEM) in SmartPLS version 3.3.3 was used to analyse the data. The model was evaluated using a two-stage approach to assess formative and reflective constructs. The analysis showed that communication and coordination practices significantly enhanced safety compliance and participation. Among these, safety compliance had a statistically significant negative relationship with adverse safety outcomes. Mediation analysis confirmed that safety compliance played a key role in linking communication and coordination to safety outcomes, indicating that improvements in communication and coordination reduce incidents primarily by fostering better adherence to safety procedures. The results highlight the importance of collaboration and communication as proactive strategies for influencing employee behaviour and lowering unfavourable safety outcomes. One important mediating component surfaced was safety compliance, confirming that management’s coordination and communication efforts work best when they promote constant adherence to safety regulations. In order to foster a culture of safety and operational excellence, organisations in high-risk industries should prioritise establishing transparent, organised communication channels and methodical coordination efforts. These strategies can reduce accidents, injuries, and lost-time incidents while producing quantifiable increases in participation and compliance.